The Impact of Financial Inclusion on Income Equality and the Prospect of Cashless Policy for Economic Resilience in Nigeria (Jurnal Lemhannas RI, 2024)
Purpose: This research investigates the impact of financial inclusion on income equality and examines the prospect of a cashless policy for economic resilience in Nigeria. The study explores whether financial inclusivity could enhance income equality and assesses the effectiveness of the Central Bank of Nigeria's cashless policy.Study Design/Methodology/Approach: The research employed various statistical techniques, including fixed effect Instrumental Variable Regression (IVR), Instrumental Variable Quantile Regression (IVQR), and Logit regression. These methods were used to analyze the relationship between financial inclusion and income equality, as well as the feasibility of the cashless policy in Nigeria.Findings: The results demonstrate that financial inclusion significantly influences household income equality, particularly among lower-income groups. However, the impact of financial inclusion on income equality is not uniform across different levels of financial inclusion. Additionally, while financial inclusion shows promise for reducing inequality at lower income distributions, the cashless policy has limited potential to further promote financial inclusion in Nigeria. Policymakers may need to consider alternative strategies, such as agent banking, mobile money, or financial education programs, to sustain and enhance financial inclusion.Originality/Value: This study provides critical insights into the interplay between financial inclusion and income equality in Nigeria. It also offers a nuanced evaluation of the Central Bank of Nigeria's cashless policy, highlighting the need for more inclusive and adaptive approaches to strengthen financial systems and economic resilience.
Keywords: cashless policy; economic resilience; financial inclusion; income equality